Launching first-year health sciences students into collaborative practice: Highlighting institutional enablers and barriers to success. - King, Sharla; Hall, Mark; McFarlane, Lu-Anne; Paslawski, Teresa; Sommerfeldt, Susan; Hatch, Tara; Schmitz, Cori; Bates, Heidi; Taylor, Elizabeth; Norton, Barbara (Journal of Interprofessional Care, 2017)
Developing and sustaining a comprehensive interprofessional education (IPE) curriculum infused throughout health science programmes at large post-secondary institutions requires not only champions within each program but also collaboration across professional programmes and strong support at an institutional level. The purpose of this article is twofold. First, it reports on the development of an interprofessional learning pathway, an institutional curricular model, and the pathway launch, an introductory learning experience within the context of a large post-secondary institution. The interprofessional curricular model provides a framework to connect the IPE that was previously fragmented across faculties and professional programmes into a scaffolded coherent pathway. The launch exposes students to the principles and competencies of collaborative practice. Second, it explores the dual role of enablers and barriers to IPE within the context of one institution’s 20-year experience of developing and delivering. In examining the elements that have sustained the institution’s IPE programming, it is highlighted how the seemingly positive elements (e.g., IPE champions and strong university support from central administration) have also served as hindrances within the academy potentially threatening the sustainability and institutionalisation of IPE. We anticipate that this curricular model and learning experiences will provide mechanisms to sustain and foster IPE.